Prevalencia del ameloblastoma uniquístico en pacientes de 16 a 35 años: Revisión bibliográfica - Lozano Gualán, Ruth Andrea (2022)
Unicystic ameloblastoma (UA) is a variant of ameloblastoma that represents 6% of all ameloblastomas, mainly affecting young adolescents in their second decade of life, with a mean age between 16 and 35 years of age. It has no predilection for the sex, it affects the mandible more frequently, especially the posterior region of the mandible just at the level of the third molar in relation to the unerupted tooth. It is considered the least aggressive in relation to the other variants of ameloblastoma, which allows a better response to conservative treatment. The objective of the study is to determine the prevalence of unicystic ameloblastoma in patients aged 16 to 35 years. Besides, describe the etiology, diagnosis, and treatment alternatives. This research is of an analytical nature with a qualitative approach for which it was carried out through bibliographic reviews, clinical cases, and meta- analyses obtained from indexed journals such as PubMed, Scielo, Google Scholar, Elsevier, and Lilacs. In addition, all the inclusion and exclusion criteria were taken into account. The information was analyzed and synthesized into tables, obtaining conclusions that the etiopathogenesis of unicystic ameloblastoma is unknown; clinical, radiographic, tomographic, and histopathological diagnostic methods are essential tools to establish the definitive diagnosis and the ideal treatment for said pathology according to its characteristics and prognosis